2020
DOI: 10.1021/acs.biochem.0c00800
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Mediate Folding of Primordial Hyperacidic Helical Proteins

Abstract: Polyamines are known to mediate diverse biological processes, and specifically to bind and stabilize compact conformations of nucleic acids, acting as chemical chaperones that promote folding by offsetting the repulsive negative charges of the phosphodiester backbone. However, whether and how polyamines modulate the structure and function of proteins remain unclear. In particular, early proteins are thought to have been highly acidic, like nucleic acids, due to a scarcity of basic amino acids in the prebiotic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…We envision the fixation of the amino acid alphabet as a late event in this sequence of events, as amino acids such as Trp, Tyr, Lys and Arg involve numerous enzymes in their biosynthesis and therefore likely required a DNA-based genome to retain the suite of catalysts necessary to prepare them. An important question that is worth reflecting upon (as we [20,24,104] and others [2123,2628,105] have shown) is how proteins managed to complete fairly sophisticated functions in the previous two stages without the full complement of amino acids (see below). The hallmark of this stage is the end of ‘chemical evolution’ as Darwinian biological evolution takes root thanks to the intrinsic stability of information encoded in DNA (compared to RNA), and the high (but not perfect) fidelity of polymerases which create the potential for point mutations, insertions and duplications.…”
Section: Protein Selection Without Nucleic Acidsmentioning
confidence: 99%
“…We envision the fixation of the amino acid alphabet as a late event in this sequence of events, as amino acids such as Trp, Tyr, Lys and Arg involve numerous enzymes in their biosynthesis and therefore likely required a DNA-based genome to retain the suite of catalysts necessary to prepare them. An important question that is worth reflecting upon (as we [20,24,104] and others [2123,2628,105] have shown) is how proteins managed to complete fairly sophisticated functions in the previous two stages without the full complement of amino acids (see below). The hallmark of this stage is the end of ‘chemical evolution’ as Darwinian biological evolution takes root thanks to the intrinsic stability of information encoded in DNA (compared to RNA), and the high (but not perfect) fidelity of polymerases which create the potential for point mutations, insertions and duplications.…”
Section: Protein Selection Without Nucleic Acidsmentioning
confidence: 99%
“…Where characterized in more detail, assistance of salts, metal ions, or cofactor binding were found to explain the folding properties 15,18,45,47 . In addition, Despotovic et al recently confirmed that folded conformations of a highly acidic 60-residue protein can be induced by positively charged counterions, in case of Mg 2+ the reported concentration corresponding roughly to its concentration in the CFPS reaction (∼10mM) 48 . In parallel, the Hecht group reported that binding of metal ions (with high nanomolar to low micromolar affinity) is a surprisingly frequent property of unevolved sequences and therefore does not require much sequence optimization 49 .…”
Section: Discussionmentioning
confidence: 91%
“…Where characterized in more detail, assistance of salts, metal ions or cofactor binding were found to explain the folding properties 15,18,42,44 . In addition, Despotovic et al recently confirmed that folded conformations of a highly acidic 60-residue protein can be induced by positively charged counterions, in case of Mg2+ corresponding roughly to its concentration in the CFPS reaction (~10mM) 45 . These studies allow us to hypothesize that the high structural propensity of the 10E alphabet could result from the cation/cofactor-rich environment, where the lack of hydrophobic and electrostatic interactions is compensated by these chemical entities.…”
Section: Structure Formation Is Comparable In Proteins From the Full Canonical Alphabet And Its Early Subset Unaffected By Chaperonesmentioning
confidence: 94%
“…While previous studies have pointed out that acidic proteins can be soluble and sustain secondary structure information, it has generally been unclear how those proteins can form compact architectures and/or interact with the highly acidic nucleic acids (Doi et al 2011;Tanaka et al 2011;Longo et al 2013;Shibue et al 2018;Newton et al 2019;Solis 2019). A recent study by the Tawfik group suggested that polyamines and divalent cations may have played an important role in promoting the folding of such early proteins (Despotović et al 2020). Similarly, magnesium cations clearly play a special role in the ribosomal structure, a molecular fossil that reports on the earliest interactions between RNA and proteins (Petrov et al 2011).…”
Section: Discussionmentioning
confidence: 99%